2010
DOI: 10.1007/s10803-010-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

Response Inhibition in Adults with Autism Spectrum Disorder Compared to Attention Deficit/Hyperactivity Disorder

Abstract: Autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD) are hypothesised to involve core deficits in executive function. Previous studies have found evidence of a double dissociation between the disorders on specific executive functions (planning and response inhibition). To date most research has been conducted with children. No studies have directly compared the stable cognitive profile of adults. It was hypothesised that adults with ASD would show generally intact response inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
8
31
0
Order By: Relevance
“…The only neuropsychological study performed in adult patients revealed significant differences between ADHD and ASDs in the Stroop task. However, using the Hayling Sentence Completion Test, which assesses verbal response inhibition, it was found that adults with ADHD did not exhibit more severe impairments compared to those with ASDs (Johnston et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The only neuropsychological study performed in adult patients revealed significant differences between ADHD and ASDs in the Stroop task. However, using the Hayling Sentence Completion Test, which assesses verbal response inhibition, it was found that adults with ADHD did not exhibit more severe impairments compared to those with ASDs (Johnston et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Another important point to note is that all but two (Iarocci and Burack 2004;Ozonoff and Strayer 1997) of the above studies reporting unimpaired inhibition in participants with autism employed prepotent response inhibition tasks in which participants have to withhold an inappropriate response that is prompted by a target stimulus (see also Johnston et al 2011). In contrast, studies that have examined resistance to distractor inhibition, in which participants have to ignore competing distractors while attempting to focus on a separate target stimulus, have tended to show clearer evidence of difficulties among individuals with autism.…”
Section: Introductionmentioning
confidence: 99%
“…Gargaro et al (2011) surmise that when using independent domains of executive functions, children with autism and those with ADHD exhibit opposite patterns (see also Pennington & Ozonoff, 1996). A recent study in adults similarly revealed potential dissociable features of executive functions between ADHD and ASD based on the Stroop, Matching Familiar Figures (MFF), and the Hayling sentence completion tests (Johnston, Madden, Bramham, & Russel, 2011). Not surprisingly, these authors conclude that evidence derived from executive functions assessments remains inconclusive and that further studies are needed (Gargaro et al, 2011; Johnston et al, 2011).…”
Section: Introductionmentioning
confidence: 99%